Prevalence of pulmonary tuberculosis in patients with diabetes mellitus and lower respiratory tract infection - Kale, Pradnya S.; Kanade, Swapna R.; Nataraj, Gita; Mehta, Preeti R. (International Journal of Research in Medical Sciences, 2020)
Background: Pulmonary Tuberculosis (PTB) still remains a global public health problem. Diabetes Mellitus (DM), is a metabolic disorder characterized by hyperglycaemia. Diabetes along with poor glycaemic control leads to an immune compromised state. As prevalence of both TB and DM is increasing in India, this association of PTB and DM may prove a threat to TB control program. Aims and objectives of the study was to detect prevalence of pulmonary tuberculosis in patients with DM and Lower Respiratory Tract Infection (LRTI). Methods: Sputum specimen from consecutive 250 known diabetic adult patients with type 2 diabetes and clinical evidence of LRTI were processed for microscopy, solid culture and Xpert MTB/RIF assay. Clinical findings, duration of DM, regularity of treatment and recent fasting blood glucose level were noted. Results: TB was detected in 31(12.8%) patients. Microscopy, culture and Xpert assay were positive in 14(5.6%), 29(11.6%) and 24(9.5%) cases respectively. Culture detected seven cases more than Xpert assay. Two additional cases were detected by Xpert assay than culture. Rifampicin resistance was detected in seven (29.17%) cases by Xpert assay. TB detection rate was higher in patients with more than two weeks of cough (14.38%), history of tuberculosis (15.9%), hyperglycemia (13.9%) and significantly higher in those with irregular anti-diabetic treatment (35.7%). Conclusions: Irregular anti-diabetic treatment, hyperglycaemia and history of tuberculosis were strongly associated with pulmonary TB. Xpert assay should be used as the initial diagnostic test for detection of tuberculosis as well as rifampicin resistance in diabetic patients by TB control programme.